Computação ciente de contexto aplicada ao monitoramento de condições críticas em ambientes físicos - Kudo, Taciana Novo (Universidade Federal de São Carlos, 2004)
Context-aware computing investigates applications that adapt their behavior according to information (or context) captured from a physical and/or computational environment such as the location of a user. The monitoring of critical conditions in physical environments is one of the domains that take advantage of the context-aware computing facilities, where context is captured from sensors spread over environments in order to aid the prevention, the combat and the evaluation of emergency situations such as fire, rebellions in penitentiaries, explosions and leaks of toxic substances. Related works report the need for a middleware that provides services, e.g. for context interpretation and location of people and objects, which can be used by a myriad of devices and any kind of applications for monitoring of critical conditions, regardless platform, operating system and/or programming language. This work presents an approach exploiting context-aware computing in the monitoring of critical conditions in physical environments, which includes the specification of a middleware and its following main services: the Context Interpreter Service, the Event Notification Service and the Location Service. The Context Interpreter Service notifies and interprets context gathered from sensors. As those interpretations follow the security policies of each business, an Interface for Configuration and Monitoring was also developed as a means to allow particular criteria of monitoring for a business. The Event Notification Service uses the publish/subscribe paradigm based on topics. The Location Service handles the location of people and objects in physical environments. Middleware components and applications communicate through XML-encoded messages via publish/subscribe mechanism. A case study for that approach uses the Asas de um Sonho aviation museum of the TAM air company as scenario.
Keywords: Teoria da informação; Computação ubíqua; Computação ciente de contexto; Segurança crítica; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO